Factors Contributing to the Development of the Retail Banking Services in Hanoi, Vietnam - Do, Huu Hai (ĐHKT, 2016)
This study focuses on factors contributing to the development of the retail banking services in Hanoi, Vietnam. A four factor model is established, corresponding to four hypotheses in this paper. Based on a sample size of 615 customers and through a multiple regression analysis, results show that IT infrastructure - service channels and tangibles are factors contributing to the development of the retail banking services in Hanoi, Vietnam…